2019
DOI: 10.1038/s41598-019-50663-6
|View full text |Cite
|
Sign up to set email alerts
|

Smart meta-superconductor MgB2 constructed by the dopant phase of luminescent nanocomposite

Abstract: On the basis of the idea that the injecting energy will improve the conditions for the formation of Cooper pairs, a smart meta-superconductor (SMSC) was prepared by doping luminescent nanocomposite Y2O3:Eu3+/Ag in MgB2. To improve the superconducting transition temperature (TC) of the MgB2-based superconductor, two types of Y2O3:Eu3+/Ag, which has the strong luminescence characteristic, with different sizes were prepared and marked as m-Y2O3:Eu3+/Ag and n-Y2O3:Eu3+/Ag. MgB2 SMSC was prepared through an ex situ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 56 publications
1
23
0
Order By: Relevance
“…The optimal doping concentrations for a MgB 2 , b MgB 2 , and c MgB 2 were 0.5%, 0.8%, and 1.2%, respectively. The corresponding ΔT cs were 0.4 K, 0.9 K, and 1.2 K, which exhibit significant improvements compared with the ΔT cs (0.2–0.4 K) in previous work [ 36 , 37 , 38 , 39 , 40 ]. Such an improvement of T c is a novel property given that all the experiments before our work confirmed that doping a second phase decreased the T c of MgB 2 .…”
Section: Introductionmentioning
confidence: 59%
See 3 more Smart Citations
“…The optimal doping concentrations for a MgB 2 , b MgB 2 , and c MgB 2 were 0.5%, 0.8%, and 1.2%, respectively. The corresponding ΔT cs were 0.4 K, 0.9 K, and 1.2 K, which exhibit significant improvements compared with the ΔT cs (0.2–0.4 K) in previous work [ 36 , 37 , 38 , 39 , 40 ]. Such an improvement of T c is a novel property given that all the experiments before our work confirmed that doping a second phase decreased the T c of MgB 2 .…”
Section: Introductionmentioning
confidence: 59%
“…The results obtained in these studies show that unlike conventional chemical doping, which consistently reduces the T c of MgB 2 , the SMSC method of doping EL materials could help increase the T c of MgB 2 . The same conclusions were drawn from substituting the inhomogeneous phase with YVO 4 :Eu 3+ or luminescent nanocomposite Y 2 O 3 :Eu 3+ /Ag [ 39 , 40 ] and replacing MgB 2 with Bi(Pb)SrCaCuO [ 41 , 42 ]. The effectiveness of improving the T c of superconducting materials through the SMSC method by doping with EL inhomogeneous phases has been proven, but the ΔT c ( ΔT c = T c − T cpure ) values obtained are generally small (0.2–0.4 K).…”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations
“…The results showed that the doping of Y 2 O 3 :Eu 3+ EL materials increases the T C of MgB 2 . We believe that the Y 2 O 3 :Eu 3+ materials generate an EL under the action of an external electric field and that EL energy injection promotes the formation of Cooper pairs; the T C of MgB 2 is improved via EL [ 35 , 36 , 37 , 38 , 39 ]. At the same time, a smart meta-superconductor B(P)SCCO consists of the B(P)SCCO matrix and an inhomogeneous phase Y 2 O 3 :Eu 3+ or Y 2 O 3 :Eu 3+ +Ag was constructed in BSCCO superconductors.…”
Section: Introductionmentioning
confidence: 99%